Analysis of the impact of coupled support for soya on surfaces and productions - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The present study proposes an analysis of how the changes and trends of soybean surfaces and produced crops have been influenced by the coupled support in the years 2015 and 2016. For this purpose qualitative and quantitative research methods will be used on the data obtained with the statistics, namely the National Institute of Statistics (NIS) and the Agricultural Accountancy Data Network (RICA), data on the total areas cultivated with soybeans and productions, respectively on the areas for which coupled support has been granted. With this data, we will determine the share of areas recorded in APIA in the total area, the dynamics of this indicator and the way in which the minimum compulsory production (for accessing the coupled support) influenced the average yield per hectare.
Keywords: Q15; Q18; 330; soybean culture; coupled support; eligible area; production